PENGARUH BERBAGAI JENIS STERILAN DAN WAKTU PERENDAMAN TERHADAP KEBERHASILAN STERILISASI EKSPLAN DAUN KENCUR (Kaempferia galanga L) PADA TEKNIK KULTUR IN VITRO - Anis Shofiyani; Agus Mulyadi Purnawanto; Reza Zahara Abdul Aziz (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2020)
This study aims to determine the effect of sterile and immersion duration on the success of sterilization of kencur (Kaempferia galanga L) leaf explants using in vitro culture techniques and to find out the types of contaminants that emerge. The study was conducted from October 2018 to February 2019, located at the Basic Agrotechnology Laboratory and Plant Engineering Laboratory, Faculty of Agriculture, Universitas Muhammadiyah Purwokerto. The design used was a randomized block design (RBD) with 15 treatments. Each treatment was repeated 3 times. The treatments were the immersed in 6% chlorine for 10 minutes (S1), for 15 minutes (S2), for 20 minutes (S3), the immersed in 0,1 g/ml HgCl2 for 1 minute (S4), for 3 minutes (S5), for 5 minutes (S6), the immersed in HgCl2 0,2 g/ml for 1 minute (S7), for 3 minutes (S8), for 5 minutes (S9), the immersed in HgCl2 0,3 g/ml for 1 minute (S10), for 3 minutes (S11), 5 minutes (S12), immersed in dithane 2 g/l for 1 hour (S13), for 12 hours (S14), for 24 hours (S15). The results showed that the treatment of Dithane sterile 2 g/l water with an immersion duration of 1 hour (S13) significantly affected the percentage of contamination and succeeded in reducing contamination by 44.44%, while the use of chlorine sterile and HgCl2 had no significant effect. The types of contaminants that appear are Macrophomoina sp., Aspergillus sp., Cladosporium sp., And Pseudomonas sp.